2010
DOI: 10.1007/s11032-010-9470-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a novel chimeric HMW glutenin subunit gene 1Dx5′ from a common wheat line W958

Abstract: A novel chimeric high-molecular-weight (HMW) glutenin subunit gene from a new common wheat line W958 (2n = 6x = 42) was isolated and characterized. SDS-PAGE analysis revealed that this glutenin subunit has similar electrophoretic mobility to 1Dx5, so it was designated 1Dx5 0 . Genomic DNA from W958 was amplified and a 2,505-bp fragment was obtained. The 1Dx5 0 subunit showed a chimeric primary structure of 1Dx5 and 1Dx2, with the 1Dx5 sequence in the 5 0 and middle repetitive regions and the 1Dx2 sequence in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…According to the BLASTN program from the National Center for Biotechnology Information nucleotide sequence database (http://blast. ncbi.nlm.nih.gov), the candidate genes TraesCS1A01G317500, TraesCS1B01G330000, and TraesCS1D01G317300 were consistent with the globulin loci reported by Gu et al [50]; TraesC-S1A01G466100LC and TraesCS1A01G466500LC were consistent with the 1Ax and 1Ay null genotpyes of the Glu-A1 locus [50,51], respectively; TraesCS1B01G570600LC was consistent with the y9 subunit of the Glu-B1 locus [52]; and TraesCS1D01G435600LC and TraesCS1D01G435700LC were consistent with the x5 and y10 subunits of the Glu-D1 locus [53,54]. Numerous studies have identified associations between the HMW-GS and the quality of wheat [2; 16; 17; 23; 25; 26; 55; 56].…”
Section: Plos Onesupporting
confidence: 78%
“…According to the BLASTN program from the National Center for Biotechnology Information nucleotide sequence database (http://blast. ncbi.nlm.nih.gov), the candidate genes TraesCS1A01G317500, TraesCS1B01G330000, and TraesCS1D01G317300 were consistent with the globulin loci reported by Gu et al [50]; TraesC-S1A01G466100LC and TraesCS1A01G466500LC were consistent with the 1Ax and 1Ay null genotpyes of the Glu-A1 locus [50,51], respectively; TraesCS1B01G570600LC was consistent with the y9 subunit of the Glu-B1 locus [52]; and TraesCS1D01G435600LC and TraesCS1D01G435700LC were consistent with the x5 and y10 subunits of the Glu-D1 locus [53,54]. Numerous studies have identified associations between the HMW-GS and the quality of wheat [2; 16; 17; 23; 25; 26; 55; 56].…”
Section: Plos Onesupporting
confidence: 78%
“…Wang et al (2012a) also predicted that the secondary structure of the 1Dx3 t subunit has a significantly higher α-helix and β-strand contents, indicating it might have positive effects on dough quality. Feng et al (2011) isolated and characterized a novel chimeric HMW-GS, Dx5 / , from wheat line W985. This subunit has six helices and one strand, including four helices in the repetitive domain capable of enhancing the dough properties, and possibly having a high potential for quality improvement.…”
Section: Molecular Characterization and Structural Featuresmentioning
confidence: 99%
“…Previously, the presence of extra cystenin residue in the repetitive domain was found in 1Dx5 and 1Ax2* B subunits, which has been associated with the superior bread-making quality (Ciaffi et al 1993;Lafiandra et al 1993;Juhász et al 2003;Feng et al 2011). Compared to 1Dx2, a serine changed to cysteine residue at the front of the repetitive domain of 1Dx5.…”
Section: Discussionmentioning
confidence: 99%